Dictionary of Encounter : Basic Terms in Christianity and Islam - Albayrak, Halis; Antes, Peter; Heinzmann, Richard; Selçuk, Mualla; Thurner, Martin (Schöningh, Fink and mentis Religious Studies, Theology and Philosophy E-Books Online, Collection 2025, 2025)
The Dictionary of Encounter juxtaposes a Christian and a Muslim view of their own religion. Theologians from Germany and Turkey explain the basic concepts of their religions, presenting them side by side and thus inviting readers to better understand their own and other religions. An indispensable guide for Christians and Muslims living together in a plural democratic society.